Uric acid independently correlates with sex-hormone binding globuline in postmenopausal women: Relationship between uric acid and SHBG - Klisic, Aleksandra; Scepanovic, Andjelka; Kavaric, Nebojsa; Ninic, Ana (Progress in Nutrition, 2019)
Background/Aim: Low sex-hormone binding globuline (SHBG) and high uric acid level are shown to be the independent predictors of many cardiometabolic diseases. However, it is unknown whether this two biomarkers are interrelated, and if so, whether this relationship is independent or it is mediated by some whether these factors. Therefore, the aim of the current study was to examine the potential relationship between serum SHBG and uric acid levels in the cohort of postmenopausal women. Methods: A total of 150 postmenopausal women encompassed this cross-sectional study. Biochemical and anthropometric data were obtained. Results: In univariate ordinal regression analysis, uric acid (Odds ratio (OR)=0.983, 95% Confidence Interval (CI) 0.978-0.989, p